Nama-Nama Surah Al-Qur’an: Tipologi, Metodologi, Karya, dan Maqāṣid yang Tersembunyi - Muhammad Ulinnuha (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2022)
This paper discusses the typology of the names of the surahs of the Qur'an, the methodology for their determination, the works produced by the scholars, and the maqāṣid implied by these names. By using the type of qualitative research library research, data processing using descriptive-analytic and maqāṣidī and socio-historical approaches, it can be seen that the source of naming the surah is taken from the beginning of the word, the main theme of the surah, foreign and unique terms, and the names of the characters. Typologically, each surah has various names. There are suras that have one name, some surahs are mentioned in one name, and some have more than one name. From the editorial side, these names are in the form of letters, isim, and fi'il. The methodology for determining the surah is carried out in three ways; through the guidance of the Prophet (tauqīfī), the ijtihad of sahabah or tabi'in, and a combination of the two. Meanwhile, works around this theme can be classified into three models, namely intact works, part of book chapters, and works for the benefit of academic assignments. From the maqāṣid aspect, each name has a purpose and message that is always inherent in the main theme of the surah. Even these names hint at the rules of life, both individually and communally, as well as socio-religious, national and civilized